Factors affecting financial well-being of millennials: a systematic review - M. Lambert, Ma. Jesusa Corazon; Md Jusoh, Zuroni; Abd Rahim, Husniyah; Zainudin, Norzalina (AMH International, 2023)
Financial well-being (FWB) refers to a status of an individual equipped with adequate resources to live life comfortably. Millennials, a cohort born in 1980-2000, fared less well financially than other generations. This article attempted to look into the existing body of knowledge to provide a comprehensive understanding of the factors affecting FWB among millennials. Employing a combined PICO and SPIDER tools, fifteen articles have been identified and subsequently, five themes were developed affecting FWB among millennials such as financial behavior and financial literacy, personal traits, social and economic environment, and life stage attributes. Among these identified factors, financial literacy is considered to be the strongest as higher financial literacy translates into better handling of finances, resulting in surplus and therefore better FWB. Financial behavior and financial attitude are also important as they involve skills, motivation, and confidence to apply knowledge and understanding. Personality traits equally remained as strong predictors along with social and economic environment factors as well as social support from firms and institutions which significantly affect financial well-being. This research will enable millennials to improve their financial lives. In the pursuit of improving their financial well-being, individuals make financial decisions to grow their assets and protect their resources and alleviate financial crises. Overall, this paper has demonstrated the factors that substantially determine FWB among millennials. It is recommended that relevant research be done to verify the factors identified in this study.